Reduction in Incidence of Ampicillin Rash by Purification of Ampicillin - Knudsen, E. T. (1970)
Purification of ampicillin (Penbritin) with respect to protein impurities has been found significantly to reduce the incidence of rashes in treated patients. This may be related to findings in animals that injections of the isolated protein impurity can induce the formation of circulating IgG antibodies and skin-sensitizing antibodies.